Representasi Simbolik Film Kartun “Dora the Explorer”: Ethnographic Content Analysis - Chaerowaty, Dede Lilis (FIkom Unisba, 2007)
Dora the Explorer marked a new trend in children media throughout the world due to its educational purposes. There weren’t many cartoon nowadays which free from violent materials. Dora the Explorer, made in US but is delivered originally in Spanish, won the hearts of parents and teachers. A textual research employing Ethnographic Content Analysis (ECA) toward Dora the Explorer showed that the story are framed within strong moral values, such as affection, friendship, helping each other, caring and giving. The main characters of Dora the Explorer consisted of Dora and his monkey pet, Boots—representing protagonist characters. Meanwhile, there is Swiper who was cast to represent bad character. The language is translated in Bahasa Indonesia, complete with strong emphasis in positive language to mark Dora’s success enforcing good morals and good behavior. By applying social learning theory, this research further revealed that children do learn Spanish language and mathematical concept from Dora’s.